1993
DOI: 10.1002/prs.680120103
|View full text |Cite
|
Sign up to set email alerts
|

Statistical evaluation of Lower Flammability Distance (LFD) using four hazardous release models

Abstract: Using four hazardous dispersion models, the ability to predict Lower Flammability Distance (LFD), the distance from a release through which the released gas is present in concentration below flammable range, has been evaluated using a set of large‐scale propane release field experiment data. The four models evaluated were the DEGADIS model, the SLAB model, the OME Simple Gas model and the OME Heavy Gas model (1983). The observed LFDs were compared with the predicted LFDs for three atmospheric conditions. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 6 publications
(1 reference statement)
4
43
0
Order By: Relevance
“…To determine the reliability of the model, the criteria used is as set in a study by Kumar et al (1993) and Chang et al (2004). According to Kumar et al (1993), the performance of the model can be deemed as acceptable if; NMSE < 0.5 and -0.5 < FB < +0.5…”
Section: Results and Discussion Overall Performance Of Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the reliability of the model, the criteria used is as set in a study by Kumar et al (1993) and Chang et al (2004). According to Kumar et al (1993), the performance of the model can be deemed as acceptable if; NMSE < 0.5 and -0.5 < FB < +0.5…”
Section: Results and Discussion Overall Performance Of Modelsmentioning
confidence: 99%
“…According to Kumar et al (1993), the performance of the model can be deemed as acceptable if; NMSE < 0.5 and -0.5 < FB < +0.5…”
Section: Results and Discussion Overall Performance Of Modelsmentioning
confidence: 99%
“…Kumar and Gudivaka [40] have discussed in detail the statistics relevant to model evaluation and has applied it to heavy gas models. Similarly, Kumar et al [41] has used statistical tools to evaluate the prediction of lower flammability distances. Patel and Kumar [42], Kumar et al [43], and Kumar et al [44] have indicated that Mean Absolute Error (MAE), Factor of Two (Fa2), Root Mean Square Error (RMSE), Fractional Bias (FB), and Normalized Mean Square Error (NMSE) are important parameters to assess the performance of air-quality models.…”
Section: Other Comparative Error Measuresmentioning
confidence: 99%
“…As expected in the real life, the shear layer model is not a perfect model. However, the acceptable range for NMSE and FB for an air quality model suggested by Kumar et al (1993) is given as, NMSE ≤ 0.5 and -0.5 ≤ FB ≤ 0.5. The values of NMSE and FB for shear layer model in all wind conditions were within acceptable limits.…”
Section: Statistical Parametermentioning
confidence: 99%